Banking systems, restructuring tools and policies applicable in the banking industry and a close examination of a restructuring event in the Turkish banking system - Yurttadur, Mustafa (My University, 2004)
In this study, after investigating the world banking systems under certain main topics, it has been emphasized the issue of restructuring, which is necessary and critical for the solution of problems and crises lived in the banking sector. Among the subjects covered in the study are what restructuring means and for what circumstances it is needed. Afterwards, the major methods used in restructuring and the subtitles of these methods have been explained. Meanwhile, the matters of how these restructuring methods are applied and which method is effective in which fields have been examined and focused. In the last part, it has been concluded that the economic crises lived in the Turkish economy have affected the banking sector and many banks have become problematic banks as a result of these effects on the sector. In addition to that, the restructuring case of a bank which was affected by the inverse developments experienced in the banking sector due to the economic crises has been analyzed and this analysis has been taken as an application. In conclusion, the restructuring studies performed either in our country or in other countries are very important for banks to work efficiently end effectively. Through effective restructurings, banks can get the chances to solve their own problems and serve better to their clients. Banks should carefully determine their before-crisis and post-crisis strategies taking into account the lessons they have got from the previous crises lived.

Bu çalışmada dünya bankacılık sistemlerinden ana başlıklar halinde bahsedilmesinin ardından bankacılık sektöründe yaşanan krizlerin ve problemlerin çözümleri için gerekli olan yeniden yapılandırma üzerinde durulmuştur.Yeniden yapılandırmanın genel anlamda ne olduğu ve hangi durumlarda bankanın yapılandırılmasının gerekli olduğu da anlatılan diğer bir konudur.Bunların ardından banka yeniden yapılandırılmasında kullanılan yöntemler ve bu yöntemlerin alt başlıklarından sırasıyla bahsedilmiştir.Aynı zamanda kullanılan yöntemlerin nasıl uygulandığı da anlatılmakta ve hangi yöntemin bankacılık sektöründe hangi alanlarda etkin olduğu da vurgulanmaktadır.Son bölümde ise Türk ekonomisinde yaşanan krizlerin bankacılık sektörünü de etkilediği ve bu olumsuz etkilenmenin sonucunda da birçok bankanın problemli hale geldiği anlatılmıştır.Bununla birlikte Türk bankacılık sektöründeki olumsuz gelişmelerin etkilediği bir bankanın yeniden yapılandırması incelenmiş ve bu inceleme çalışmada bir uygulama olarak anlatılmıştır.Kısaca gerek ülkemizde gerekse diğer ülkelerde bankacılık sektöründe yapılan yeniden yapılandırma çalışmaları bankaların sistemde verimli ve etkin çalışabilmesi için oldukça önemlidir.Zamanında ve yerinde yapılan yapılandırmalarla bankalar problemlerini en kısa zamanda çözerek müşterilerine olan görevlerini yerine getirmektedirler.Bankalar daha önce yaşanan krizlerden ders alarak kriz anındaki ve sonrasındaki stratejilerini iyi belirlemelidir.
Keywords: Banka ve bankacılık; Bankalar ve Bankacılık; Ekonomi; Finansman ekonomisi